Internal and external inflammatory root resorption: Report of two cases and their endodontic management - Arun Singh; Sharanya A J; Promila Verma; Rhythm Bains (Journal of Healthcare Research and Education, 2026)
Inflammatory root resorption is a pathological condition that can lead to progressive loss of tooth structure and eventual tooth loss if not diagnosed and treated at an early stage. It may occur as internal inflammatory root resorption (IIR), originating from the pulp, or external inflammatory root resorption (EIR), arising from the periodontal ligament, with both conditions commonly associated with persistent microbial infection. Accurate diagnosis and elimination of the infectious stimulus are essential for arresting the resorptive process and preserving the affected tooth. This report presents two cases of inflammatory root resorption successfully managed by nonsurgical endodontic treatment. The first case involved a 25-year-old female who presented with pain in the maxillary left lateral incisor. Clinical examination, radiographic evaluation, and cone-beam computed tomography (CBCT) confirmed a non-perforating internal inflammatory root resorption associated with symptomatic apical periodontitis. Root canal treatment was performed using calcium hydroxide as an intracanal medicament, followed by obturation with gutta-percha and mineral trioxide aggregate (MTA). The second case involved a 24-year-old female with pain in a previously treated mandibular first molar. Radiographic examination revealed external inflammatory apical root resorption associated with persistent periapical infection. Nonsurgical retreatment was carried out using sequential intracanal medicaments, followed by MTA obturation because of severely resorbed open apices. Both patients remained asymptomatic during follow-up, and radiographic evaluation at 12 months demonstrated healing of the periapical lesions and arrest of the resorptive process. These cases highlight the importance of early diagnosis, careful differentiation between internal and external inflammatory root resorption, and the use of advanced imaging when indicated. Contemporary nonsurgical endodontic treatment, incorporating effective canal disinfection and bioactive materials such as MTA, can successfully arrest inflammatory root resorption and preserve natural teeth with favorable long-term outcomes.